Further interpretations of real-life events ebook A story from further interpretations of real-life events. - Moffett, Kevin (2012)
In the title story from Kevin Moffett's dazzling new collection, Further Interpretations of Real-Life Events, a young, struggling writer discovers that his father has begun to publish short stories—good ones, too—under the son's own name. The result is a brilliant and occasionally hilarious look at the meeting point of creative anxiety and the combustible father-son relationship.